Kebijakan Komunikasi dalam Organisasi DPM Dikampus II IAKN - Jalin Tarida Juanda Sitinjak; Raikhapoor Raikhapoor (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In the era of globalization and rapid development of information technology, communication is a crucial element in supporting the success of organizations, including within the scope of the Student Representative Council (DPM) of the Tarutung State Christian Institute. As a student legislative body, DPM has the task of forming regulations, overseeing the implementation of policies, and carrying out supervisory functions over the executive budget institution. However, communication challenges often hinder the effectiveness of DPM's performance, such as the lack of integrated communication channels, low understanding of organizational communication, and information gaps between DPM, students, and the campus. Therefore, an innovative communication policy is needed, both internally and externally. Internally, this policy must encourage openness, transparency, and collaboration between members. Externally, an effective communication strategy will strengthen the relationship between DPM, students, and the campus, so that the legislative function can run optimally and create a synergistic relationship.